Exploring the Rich Tapestry of Cultural Identity in Selected Siswati Short Stories - Khulisile Judith Nkuna; Innocent Zitha (E-Journal of Humanities, Arts and Social Sciences)
This paper aimed to examine the function of Siswati short stories in promoting cultural identity through an analytical lens. The researchers meticulously collected data from a diverse array of sources, such as online platforms, scholarly journals, library books, and articles. Subsequently, the thematic analysis was employed to critically and qualitatively analyse the function of Siswati short stories in advancing cultural identity. The findings exhibit that Swati people’s customs and beliefs are sustained because elders transmit wisdom and knowledge to younger generations through the art of storytelling. Siswati folktales weave together parts of mythology, folklore, and daily life to provide a nation and restore a sense of pride and belonging in its people. However, upholding conventional values and social conventions is one of the main purposes of Siswati short stories. On this basis, these tales frequently touch on issues of deference to elders, harmony within the community, and the value of community cohesion. These tales are essential in forming the social and cultural fabric of society, serving as a means of moral instruction and a means of remembering the traditions and celebrations of the Swati people. The contribution of this paper, Swati short stories, is a valuable instrument for preserving a harmonious and cohesive community by teaching cultural values and ethics in the minds of their readers through the fascinating narrative style of these moral lessons.